Pneumatic measurement of intraocular pressure: interp´retaion of hypobaric and hypoxic effects - Cymerman, Allen; Fulco, Charles S.; Lyons, Timothy P.; Muza, Stephen R.; Rock, Paul B. (Acta Andina, 2025)